The Improvement of the Survival, Growth and Production of Vaname Shrimp (Litopenaeus vannamei) and Seaweed (Gracilaria verucosa) based on Polyculture Cultivation - Titik Susilowati; Johanes Hutabarat; Sutrisno Anggoro; Muhammad Zainuri (International Journal of Marine and Aquatic Resource Conservation and Co-existence, 2014)
The presence of aeration on the cultivation of polyculture system can eliminate oxygen depletion at night while the intensity of light would effect the seaweed Gracilaria verucosa to perform photosynthesis. The supplies of oxygen is to eliminate the oxygen depletion at night until morning, and propose the efficiency of feeding activity, and also stabilize the water quality. The purpose of this research is to improve the survival, growth and production of vaname shrimp, and Gracilaria verucosa. This research was conducted in Jepara Brackishwater Aquaculture Research and Development Center (BBPBAP), from May until August 2013. A number of 75 shrimps and 1,750 g Gracilaria vericosa were cultivated in the 800 L tank, which observed for 96 days. There are four type of treatments, oxygen supply O1 (3,500 lux light intensity), O2 (Aeration with 700 mL minute-1 speed), O3 (light intensity and aeration), O4 (without light and aeration), three replications. This research was conducted using an experimental Randomized Block Design. The survival rate and growth of shrimp (Litopenaeus vannamei) showed a highly significant (p < 0.01) different between the treatments, while the growth and biomass production of seaweed (Gracilaria verucosa) showed a significantly (p < 0.05) different. The three treatments of oxygen and light supply, aeration and the combination of light and aeration, it can be concluded that survival, growth and production of vaname shrimp and Gracilaria verucosa. The combination of light and aeration treatment is the best, it can be concluded survival rate of shrimp (94.64%) compare to the treatment without oxygen (45.24%). Absolute growth rate of shrimp increased from 9.57 g to 12.97 g. The specific growth rate of shrimp increased from 4.73% to 5.07%. The biomass production of shrimp increased from 181.56 g m-2 to 883.95 g m-2. The combination of light and aeration can improve the absolute growth rate of Gracilaria verucosa from 25.86 g to 52.724 g. The specific growth rate of seaweed increased from 1.77% to 2.64% then biomass production of Gracilaria verucosa also to increase from 2,557.76 g to 5,063.2 g. Key words: Litopenaeus vannamei, Gracilaria verucosa, oxygen supply